Spatial and temporal considerations of implementing local renewable energy sources and decentralised heat recovery for domestic heat. (15th July 2022) - Liu, F.; Schellart, A.; Shepherd, W.; Boxall, J.; Mayfield, M.; Tait, S.
Abstract: A UK case study area containing over 33, 000 households has been used to investigate spatial and temporal conflicts in meeting domestic heat demand through renewable electrical energy supply and low-grade decentralised heat recovery from the urban drainage network. The case study area was selected as its water infrastructure and population density were representative of the conditions experienced by the majority of the UK's urban population. The findings suggest that adopting an optimised and integrated water-energy system would lead to a 60% reduction in current carbon emissions, compared to a natural gas based system. The integrated water-energy system proposed for domestic heating showed an annual surplus of renewable energy of 716 GWh. However, a non-renewable source of energy of 114 GWh is required to deal with the intermittency of the demand and renewable energy supply. Given the renewable surplus, it would be possible to eliminate carbon emissions from domestic heating with the addition of local low efficiency inter-seasonal energy storage. Taking a broader perspective, the calculated 60% carbon emission saving is significant as the domestic housing sector contributes 15% of the UK carbon emissions. A progressive adoption of such locally based schemes throughout the country would be able to make tangible reductions to national carbon emission targets. Highlights: Quantified spatio-temporal patterns of energy supply and heat demand 33, 000 households. Optimised integrated water-energy system reduced domestic heating CO2 emissions by 60%. Considerable annual surplus of renewable energy and low-grade heat given heat demand. Sub daily energy supply-demand imbalances occur throughout whole year. Relatively low-efficiency thermal energy storage could mitigate imbalance.